Sacred Traditions, Digital Transitions: Exploring English Teachers’ Experiences in Bridging Faith and Technology in Pesantren - Hertiki; Eliasanti Agustina; Rahmat Setiawan; Meytha Dwi Kurniadiansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research scrutinizes how three English teachers in Islamic boarding schools (pesantren) located in Ngawi, East Java, Indonesia, negotiate the integration of digital technology within a framework of sacred values and pedagogical practice. Employing a narrative inquiry approach, the research draws on semi-structured interviews conducted between June and October 2025 to capture teachers’ life experiences in navigating institutional norms and moral expectations. Data were analyzed thematically following Braun and Clarke’s (2006) framework to identify recurring patterns of ethical reflection and pedagogical decision-making. The findings demonstrate that digital technology in pesantren is not understood as a neutral instructional instrument but as a moral space imbued with ethical and spiritual significance, where every pedagogical choice is evaluated against religious norms. Teachers engage in selective adaptation strategies, such as restricting open internet access, curating faith-aligned digital content, and repurposing technology for controlled activities like language performances and project-based tasks. These practices give rise to a distinctive form of value-based digital literacy characterized by spiritual awareness, ethical filtering, and pedagogical adaptability. The discussion reveals that although institutional restrictions often constrain technological innovation, they simultaneously foster teachers’ reflective agency and moral creativity. The research concludes that effective digital integration in pesantren relies less on rigid regulation than on the cultivation of ethical consciousness among teachers and students, allowing technology to function as an instrument of faith-oriented learning rather than a disruption to religious tradition.